2021
DOI: 10.1556/2060.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative/nitrative stress and uterine artery pulsatility index in early pregnancy

Abstract: IntroductionIncreased oxidative/nitrative stress is characteristic not only in pathologic, but also in healthy pregnancy. High uterine artery pulsatility index (UtAPI) at the end of the first trimester is associated with altered placentation and elevated risk for adverse pregnancy outcomes. We aimed to examine the relationship of systemic oxidative/nitrative stress and uterine artery pulsatility index in the first trimester and their correlation to pregnancy outcomes.Material and methodsHealthy pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The rest of the markers were researched in either one or two studies: 8-isoprostane ( n = 1), 8-OHdG ( n = 2), total peroxide ( n = 1), nitrotyrosine ( n = 1), 8-iso-prostaglandin F2α ( n = 2), 8-epiprostaglandin F2-α ( n = 1), prostaglandin F2α ( n = 1), thiol ( n = 1), disulphide ( n = 1), TOS ( n = 1), TAS ( n = 1), DNA damage in blood leukocytes ( n = 1), CAT ( n = 2), γ-glutamyl transferase ( n = 1), hs-CRP ( n = 1), GSH ( n = 1), NO ( n = 1), carbonyl proteins ( n = 1), superoxide anion expressed as reduced nitroblue tetrazolium ( n = 1), aldehyde dehydrogenase ( n = 1), GST ( n = 1), soluble fms-like tyrosine kinase-1 ( n = 1), and placental growth factor ( n = 1) [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the markers were researched in either one or two studies: 8-isoprostane ( n = 1), 8-OHdG ( n = 2), total peroxide ( n = 1), nitrotyrosine ( n = 1), 8-iso-prostaglandin F2α ( n = 2), 8-epiprostaglandin F2-α ( n = 1), prostaglandin F2α ( n = 1), thiol ( n = 1), disulphide ( n = 1), TOS ( n = 1), TAS ( n = 1), DNA damage in blood leukocytes ( n = 1), CAT ( n = 2), γ-glutamyl transferase ( n = 1), hs-CRP ( n = 1), GSH ( n = 1), NO ( n = 1), carbonyl proteins ( n = 1), superoxide anion expressed as reduced nitroblue tetrazolium ( n = 1), aldehyde dehydrogenase ( n = 1), GST ( n = 1), soluble fms-like tyrosine kinase-1 ( n = 1), and placental growth factor ( n = 1) [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The uterine artery PI is currently the most commonly used indicator that can best reflect the blood flow parameters of the uterine artery ( 6 9 ). In this study, when the mean PI values of the clinical pregnancy group and the nonclinical pregnancy group were compared, no statistical significance was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, increased circulating levels of biomarkers of oxidative stress were shown to associate with multiple agerelated diseases, including cancer, diabetes mellitus [21], neurodegenerative diseases, and cardiovascular diseases, as Oxidative Medicine and Cellular Longevity well as pathological conditions characterized by ongoing inflammatory processes [37,38]. On another note, nitrative stress-imposed by reactive derivatives of NO-contributes to a plethora of pathophysiological processes as well as aging [7,[39][40][41]. This study also found that concentrations of urinary biomarkers of oxidative stress varied considerably in older individuals.…”
Section: Discussionmentioning
confidence: 99%